2022
DOI: 10.37745/10.37745/ijecer.16/vol4n11532
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals pH-Mediated Microbial-Remediation in Septic Tank Effluents

Abstract: This paper studied the role of pH in the microbial remediation of heavy metals in septic tank effluents from three sample locations in the south-south region of Nigeria. The region is famous for agriculture, industrial and auto-mechanic activities leading to the uptake and bioaccumulation of heavy metal contaminants through the food chain. Heavy metals concentrations, pH, and microbial analysis in effluent samples, were determined using standard methods. The material balance approach (see Supplementary Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The results of the electrical conductivity in this study was between 417.50 ± 19.60 -794.45 ± 31.65, this high value could be as a result of the presence of high Na + and Mg + salts in the environment. This was in agreement with the research carried out by Abosede (2013), Sari et al, (2018, Oyem and Oyem (2013). The research of Abdulfattah et al (2016), Precti and Shah (2015) reported from the research on hydrocarbon contaminated soil that electrical conduct can be affected by oil pollution.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the electrical conductivity in this study was between 417.50 ± 19.60 -794.45 ± 31.65, this high value could be as a result of the presence of high Na + and Mg + salts in the environment. This was in agreement with the research carried out by Abosede (2013), Sari et al, (2018, Oyem and Oyem (2013). The research of Abdulfattah et al (2016), Precti and Shah (2015) reported from the research on hydrocarbon contaminated soil that electrical conduct can be affected by oil pollution.…”
Section: Resultssupporting
confidence: 89%
“…The significantly higher values of electrical conductivity values obtained from the various sampling site in this study could have resulted from high concentration of charged ions in the impacted sites. The research of Oyem and Oyem (2013) revealed electrical conductivity values between the range of (19.6 -145.0) µs/cm, the lower values could be as a result of the occurrence of nitrate leaching taking place in the Niger Delta. The results of the electrical conductivity in this study was between 417.50 ± 19.60 -794.45 ± 31.65, this high value could be as a result of the presence of high Na + and Mg + salts in the environment.…”
Section: Resultsmentioning
confidence: 96%